2000
DOI: 10.2527/2000.78102690x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative relationship of systemic virus concentration on growth and immune response in pigs.

Abstract: Ninety-six pigs from a herd naive for porcine reproductive and respiratory syndrome (PRRS) virus were weaned (10 +/- 3 d of age), penned individually in isolation rooms, and, at 29 +/- 4 d of age, oronasally inoculated with a 2-mL dose of 10(4.3) JA142 PRRS virus/ mL. Body weight; feed intake; and serum concentrations of PRRS virus, interferon, and alpha1-acylglycoprotein were determined for each pig every 4 d on d -8 to 24 postinoculation to quantify the effect of PRRS exposure on the immune response and grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
47
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 6 publications
8
47
1
Order By: Relevance
“…For example, virus concentration in serum and BAL were significantly related at 21 dpi, but not at 10 dpi, where virus levels were substantially greater, suggesting different time trends for the virus dynamics at different locations. Indeed, viral loads in serum are reported to peak as early as 4 dpi (Greiner et al, 2000), whereas virus load in the lung peaks at 7 to 9 dpi (Labarque et al, 2003). However, Petry et al (2005) found moderately strong positive correlations between virus concentrations in blood, lung, and lymph nodes at 14 dpi.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…For example, virus concentration in serum and BAL were significantly related at 21 dpi, but not at 10 dpi, where virus levels were substantially greater, suggesting different time trends for the virus dynamics at different locations. Indeed, viral loads in serum are reported to peak as early as 4 dpi (Greiner et al, 2000), whereas virus load in the lung peaks at 7 to 9 dpi (Labarque et al, 2003). However, Petry et al (2005) found moderately strong positive correlations between virus concentrations in blood, lung, and lymph nodes at 14 dpi.…”
Section: Discussionmentioning
confidence: 96%
“…Greiner et al (2000) and Petry et al (2005) both reported a negative relationship between serum PRRS virus concentration and BW growth. However, they also found that the strength of the relationship varied throughout the stage of infection, with the strongest correlation/greatest reduction in growth occurring at the later infection stages when systemic virus concentration was less.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These pigs were housed on a farm with intermediate health status, hence would have been exposed to some environmental pathogens. As infection can reduce performance, an increase in immunity may be expected to improve performance Balaji et al, 2000;Greiner and Stahly, 2000), provided the benefits outweigh the costs of the increased immunity. For this set of high lean growth pigs, the high WBC may reflect an ability to mount a higher immune response, the benefits of which may lead to improved lean growth, particularly in the circumstances under which they were selected, i.e.…”
Section: Selection-induced Changes In Innate Immune Traits In Large Wmentioning
confidence: 98%
“…Infections with enteric pathogens such as Salmonella or Escherichia coli are common during intensive pig production and are associated with poor performance and animal welfare (Pijpers et al, 1991;Greiner et al, 2000). Such infections may also pose a risk to human health and lead to expensive veterinarian intervention costs.…”
Section: Introductionmentioning
confidence: 99%